Changes in physico-chemical, cellular structure and antioxidant activities of Carissa congesta L. Fruit during growth and development - Mohammad, Mariani (2018)
A study on the changes in physico-chemical, antioxidant activities and cellular structure changes of Carissa congesta fruit was conducted on weekly intervals from 1 until 13 weeks after anthesis (WAA) to establish its growth pattern. A series of the mentioned trait changes was carried out in order to establish the growth pattern and its compositional changes. For these purposes, fully bloomed flowers of C. congesta were tagged. In this study, the fruits were thinned to allow only five per cluster. The experiment was conducted by using a randomized complete block design with three replications. The morphological traits (fruit length, diameter, fresh weight and volume) were subjected to logistic regression analysis. Data from the measurements of colour, firmness, chemical (soluble solids concentration (SSC), pH, titratable acidity (TA) and moisture content), physiological (respiration rate and ethylene production), phytochemical (phenolic content, anthocyanin and antioxidant activities), and mineral nutrients were analyzed by using analysis of variance while means were separated by least significant difference. Growth of C. congesta fruit at cellular level was documented by using light microscopy (LM) and scanning electron microscopy (SEM). Results showed that the fruit took approximately 100 days from anthesis until ripening. The fruit exhibited a single sigmoid growth pattern where three physiological stages (S1, S2 and S3) were identified. Cells of C. congesta fruits at S1 underwent rapid division, followed by cell expansion at S2 before it reached physiological maturity at S3. These changes were in accordance with cellular structure as observed under LM and SEM. C. congesta fruits appeared whitishpink in colour at early weeks of development before it changed to red and then dark purple at later weeks. The visual colour changes of C. congesta fruit were in line with L* C* and ho values as fruit grew and developed. Fruit firmness and TA increased initially, then decreased during ripening while SSC and pH increased as WAA progressed. Respiration rate of C. congesta fruit was high at initial stage of growth, then reduced at later stages. While no ethylene was detected throughout 13 weeks of observation. Fruits at 13 WAA exhibited the highest total antioxidant activities, phenolic and anthocyanin contents. Vitamin C content in C. congesta fruits was much higher than any other wellestablish and known fruits at any stages of growth. C. congesta fruits demonstrated high levels of nitrogen and potassium and a wide diversity of other mineral constituents throughout fruit growth and development. As conclusions, it is clear that the quality of C. congesta fruit changed as it developed, matured and reached the stage of palatability. Since C. congesta fruits constitute a good vitamin and mineral source, high phenolic and antioxidant levels, it increases the value of this fruit to be commercialized as an economic alternative to the natural food colourant or pharmaceutical production.